Cognitive Performance in Indian School-Going Adolescents Is Positively Affected by Consumption of Iron-Biofortified Pearl Millet: A 6-Month Randomized Controlled Efficacy Trial. Issue 9 (17th July 2018) - Scott, Samuel P; Murray-Kolb, Laura E; Wenger, Michael J; Udipi, Shobha A; Ghugre, Padmini S; Boy, Erick; Haas, Jere D
Abstract: BACKGROUND: Iron deficiency remains the most prevalent micronutrient deficiency globally, but few studies have examined how iron status relates to cognition in adolescents. Iron biofortification of staple food crops is being scaled up, yet it is unknown whether consuming biofortified crops can benefit cognition. Objective: Our objective was to determine the efficacy of iron-biofortified pearl millet in improving attention and memory in Indian school-going adolescents. Methods: A double-blind, randomized, intervention study was conducted in 140 Indian boys and girls, aged 12–16 y, who were assigned to consume iron-biofortified [Fe = 86 parts per million (ppm)] or conventional (Fe = 21–52 ppm) pearl millet. Hemoglobin, ferritin, and transferrin receptor (TfR) were measured and body iron (BI) was calculated at baseline and after 4 and 6 mo. Five measures of cognitive function were obtained at baseline and 6 mo: simple reaction time (SRT), Go/No-Go (GNG) task, Attentional Network Task (ANT), Composite Face Effect (CFE) task, and Cued Recognition Task (CRT). Intention-to-treat analysis was used. Results: Daily iron intake from pearl millet was higher in those consuming biofortified compared with conventional pearl millet (19.6 compared with 4.8 mg/d). Effects on ferritin, TfR, and BI at 4 mo, and on TfR at 6 mo (all P  < 0.05), indicated efficacy of biofortified pearl millet over conventional pearl millet in improving iron status. Compared with conventional pearl millet, the consumption of biofortified pearl millet resulted in greater improvement in attention (SRT, GNG, and ANT) and memory (CFE and CRT). Reaction time decreased twice as much from 0 to 6 mo in those consuming biofortified compared with conventional pearl millet on attention tasks (SRT: −123 compared with −63 ms; GNG: −67 compared with −30 ms; ANT double cue: −74 compared with −32 ms; all P  < 0.01). Conclusion: Consuming iron-biofortified pearl millet improves iron status and some measures of cognitive performance in Indian adolescents. This trial was registered at http://www.clinicaltrials.gov as NCT02152150.